Fatores que interferem no processo de trabalho e nas relações interpessoais: percepção dos servidores de enfermagem de um serviço ambulatorial. - Batista, Anselma Alves (2013)
The current changes in society as well as the human dimension in health care institutions call for the importance of interpersonal relationships in order to find a balance in the work process in health care. The objective of this study is to evaluate the factors interfering with both the work process execution and the interpersonal relationships among the nursing professionals aiming at improving the ambulatory specialty services. The research was carried out at the Walter Cantídio University Hospital (HUWC) at the Federal University of Ceará - UFC. The methodology chosen was that of an exploratory and qualitative type research. Data was collected through an interview containing questions about work relationships as well as the factors interfering with the work process. The questionnaire was applied to 23 nurses who have been working at the institution for more than 20 years in direct contact with the population. Results analysis was based on Bardin’s (1977; 2006) Content Analysis Method. This project has received the HUWC Research Ethics Committee’s favorable opinion under approval N. 15237313.13.2.0000.5045, with all the participants signing the informed consent form. Data collection was carried out from June 5th to July 15th, 2013. The results analysis led to the conclusion that the factors interfering with the nursing professionals work process derive from two dimensions: the Personal Dimension and the Institutional Dimension. The Personal Dimension described work satisfaction as a subjective aspect, empathy with co-workers, respect, institutional links, and demand for more human resources actions regarding collective matters. The Institutional Dimension described issues related to the non-compliance with demands, shortage of material, insufficient equipment, information failure, inefficient communication and environmental conditions. This results in the need for more investment in the physical infrastructure such as shower and hygiene facilities, meeting rooms, work gymnastics facilities, leisure activities, a snack room, etc. It also shows the importance of the connection between the human resources management and continuing education regarding the daily life of the ambulatory care nursing team through an effective follow-up.